Proses Penyidikan dalam Sistem Peradilan Pidana - Mutia Hafina Putri; Akhmad Munawar; Muhammad Aini (Jurnal Hukum Lex Generalis, 2023)
Investigation is a crucial stage in criminal law to find the suspect, as stipulated in Article 1 paragraph (2) of the Criminal Procedure Code and the Chief of Police Regulation Number 6 of 2019. However, Articles 14 paragraphs (2), (3), and (4) of this Police Regulation demonstrate inharmonicity. Paragraph (2) states that a suspect can be determined in the Investigation Commencement Order (SPDP), while paragraph (3) states the opposite. Paragraph (4) regulates the notification of a suspect after 7 days of issuing the Investigation Order. Ideally, the determination of a suspect should refer to Article 10 paragraph (1) of the said Police Regulation so that the criminal justice system can run more firmly and consistently.